THE EFFECT OF COW URINE AND COCOA PEEL’S COMPOST FOR THE GROWTH OF PALM OIL (Elaeis guineensis Jacq) IN THE MAIN NURSERY - Ridho Ilahi; Erlida Ariani; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Palm oil (elaeis guineensis jacq.) are still plant unseeded in the agricultural sector indonesia and especially riau. Area palm oil a plant any it increased. A nursery palm oil is the first step very the success planting in the field, this needs to be done technique cultivation capable of producing seeds quality, one through fertilization in a nursery. Research aims to understand the effects of interaction urine cows and compost rind cocoa and to get treatment best in growth seed palm oil in main nursery. Experimental research conducted at the Faculty of Agriculture University of Riau, from April to August 2015. The research uses design Completely Randomized Design (CRD) factorials consisting of 2 the test 3 and obtained unit experiment 27. Urin beef consisting of C0: without cow urine, C1: cow urine 10 ml/liter, C2: cow urine 20 ml/liter. The compost consisting of K0: without compost, K1: compost 100 g/plants and K2: compost 150 g/plant.Data were analyzed using ANOVA and continued with further test Duncan’s New Multiple Range Test (DNMRT) at 5%.The result showed that cow urine influential real against broad leaves palm oil, but influential not real against high, diameter holm and the number of midrib palm leaves. factor compost rind cocoa show real impact on high, diameter holm and the number of midrib leaves palm oil, but influential not real against broad leaves palm oil. Combination cow urine 20 ml/liter and compost 150 g/plant raise high, holm diameter, the number of midrib leaves and broad leaves palm oil. Keywords: cow urin, compost rind cocoa, oil palm, main nursery